Markedly elevated angiotensin converting enzyme in lymph nodes containing non-necrotizing granulomas in sarcoidosis. - Silverstein, E (1976)
Sarcoidosis is a disease of unknown etiology that is characterized by the generalized formation of granulomas and is accompanied by elevation in the serum in less than half the patients of angiotensin converting enzyme, a dipeptidyl carboxypeptidase that catalyzes the conversion of the decapeptide, angiotensin I, to the pressor octapeptide, angiotensin II, and L-histidyl-L-leucine. Mean activity of angiotensin converting enzyme was elevated generally more than 10-fold in granuloma-containing lymph nodes, but not in lung in which normally it is abundant, in 19 of 20 patients with sarcoidosis. Angiotensin converting enzyme in lymph nodes from subjects with sarcoidosis was similar to the enzyme from normal lung and lymph node with respect to activity as a function of pH, inhibition of activity by EDTA and o-phenanthroline, gel filtration on Sephadex G-200, and requirement for chloride for activity, but appeared to be more heat labile. The data suggest that the granulomas in sarcoidosis may be the source of the elevated serum enzyme and that cells of the granulomas, particularly the epitheloid cells which appear by electron microscopy to have active protein biosynthesis, may be actively synthesizing the enzyme.